Permafrost-related hiatuses in stalagmites: Evaluating the potential for reconstruction of carbon cycle dynamics - Lechleitner, Franziska A.; Mason, Andrew J.; Breitenbach, Sebastian; Vaks, Anton; Haghipour, Negar; Henderson, Gideon M. (Quaternary Geochronology, 2020)
Permafrost is widely present throughout the Northern Hemisphere high latitudes, and stores large amounts of carbon in the form of frozen soil organic matter. The response of permafrost regions to anthropogenic climate change remains uncertain, in part because of a lack of information on their response to past changes in global climate. Here we test the use of stalagmites from two caves in Siberia as a novel, precisely dated, and highly localised archive of past permafrost carbon cycle dynamics. Stalagmite growth at these sites is controlled by the presence/absence of permafrost above the cave over glacial-interglacial time scales. We target the transition layer between two subsequent growth phases (interglacials) and the interval directly following growth resumption after the last glacial in three stalagmites, as this is where a geochemical imprint of thaw-related processes in the frozen zone between surface and cave would be recorded. We apply a multi-proxy approach including carbon isotopes (δ13C and 14C) and trace element concentrations, combined with petrographic analyses and high-resolution U-Th chronology. Our dataset indicates complex growth patterns and possible intervals of microbial colonisation of the stalagmite surface in the transition layers. High-resolution U-Th ages confirm that the transition layer is not a single, long growth hiatus, but rather a period of extremely slow or episodic growth phases, possibly during “skipped” interglacials. However, we find no conclusive evidence for a geochemical signature related to permafrost degradation and related local carbon cycle dynamics, which might be related to insufficient sensitivity of the archive for high-frequency processes and/or insufficient measurement resolution.